Health strategies in combate and prevetions violences against women (Research, Society and Development, 2021)
Identify which technologies are being used to minimize and prevent violence against women. Methodology: This is an integrative review in which this method has the function of aggregating and summarizing research results on a specific topic or issue. The research was conducted in the BVS databases, which includes LILACS and MEDLINE, SciELO, and BDTD. As descriptors were used “Health technology” and “Violence against women” indexed in the DeCS, the Boolean operator AND was used to form the search strategy. Results: Obstetric violence is still little recognized as a violent act, and it is necessary to address your rights during pregnancy, childbirth and post childbirth. Discussion: In view of the results, it was possible to observe that technologies are tools that facilitate communication between women and health professionals, since violence against women is a multifactorial phenomenon that requires the creation of strategies for coping and prevention. Conclusion: It was observed that the use of technologies in the fight and prevention of violence against women has been of great credibility, as it facilitates the identification by professionals of these violence that greatly facilitates, thus bringing a better comfort and security for these vulnerable women than many sometimes it is difficult to expose these aggressions.